The permanent and changing side of sharia - Bakour Mohamad, Bachar (International Institute for Muslim Unity (IIMU), 2016)
As the undeniably pervasive impact of modern trends grew more entrenched in Muslim societies, the question of whether Islam is static or dynamic has reverberated in elite circles, media outlets, as well as the populace. This paper explores this issue, aiming to answer the following questions: Why and how can Sharia be dynamic? Can Islam in one respect remain static, while, in otherwise areas, calling for change and evolution? What is the Islamic rationale for change? Further, the paper maintains that Islam has essentially two cardinal aspects: the closed area, static and unchanging; and the open area, quite dynamic and changing. Both areas, this paper contends, should work side by side for the welfare of humanity, proposing the best possible solutions to the contemporary needs and conditions.